Catalyst‐Free Vitrimer Cross‐Linked by Biomass‐Derived Compounds with Mechanical Robustness, Reprocessability, and Multishape Memory Effects. Issue 21 (23rd September 2021) - Huang, Lingyun; Yang, Yinxin; Niu, Zhen; Wu, Ruiyao; Fan, Weifeng; Dai, Quanquan; He, Jianyun; Bai, Chenxi
Abstract: Vitrimerization of thermoset polymers plays an important role in addressing resource recovery and reuse. Vitrimer elastomers with good mechanical properties often require well‐designed crosslinking agents or fillers, but this increases processing complexity or reduces vitrimer dynamic properties. In this report, a simple green strategy to build a strong vitrimer elastomer is designed. Commercially available epoxidized natural rubber (ENR) is cross‐linked with biomass‐derived D‐Fructose 1, 6‐bisphosphoric acid to get a vitrimer elastomer cross‐linked by β ‐hydroxy phosphate ester bonds and has abundant hydrogen bonds. Hydrogen bonds can preferentially break and dissipate energy under external forces, which makes the sample robust. The topological network can be reformed at high temperatures through the dynamic exchange of β ‐hydroxy phosphate ester bonds, which gives the material malleability and recyclability. In addition, through the strategy of combining reprocessing and welding, multiple shape memory effects can be achieved in one postprocessing step. Considering that a variety of commercially available epoxy polymers are easily available, it is believed that this strategy can be a simple and versatile way to enable commercial epoxy polymers to achieve green crosslinking through biomass crosslink agents, which results in robust and recyclable vitrimers based on β ‐hydroxy phosphate bonds. Abstract : Commercially available epoxidized natural rubber is cross‐linked with biomass‐derived d ‐fructose 1, 6‐bisphosphoric acid to get a vitrimer elastomer cross‐linked by β ‐hydroxy phosphate ester bonds and has abundant hydrogen bonds. The combination of hydrogen bonds and β ‐hydroxy phosphate ester bonds make the sample has the characteristics of mechanical robustness, recyclability, and multiple shape memory.